The effect of a simulation-based training program in basic life support on the knowledge of Palestinian nurses: a quasi-experimental study in governmental hospitals - Yousef Fahajan; Osama J. Emad; Ahmed Hassan Albelbeisi; Ali Albelbeisi; Yasmin Abu Shnena; Ayda Khader; Edris Kakemam (BMC Nursing, 2023)
Abstract Background Basic Life Support (BLS) plays an important role in increasing the survival rate of hospitalized heart attack patients. There are no previous studies on the effect of BLS training among Palestinian nurses. This study aimed to evaluate the effect of simulation-based BLS training program on nurses’ knowledge Palestinian nurses at governmental hospitals. Methods A quasi-experimental, pre & post-test design was used. 700 nurses were recruited proportionally using a simple random sampling method among 2980 nurses from 13 public hospitals in the Gaza Strip. This study was conducted from June to August 2022. A practical BLS test consisting of 10 multiple-choice questions according to American Heart Association guidelines (2020) was collected and sociodemographic characteristics. SPSS software, version 24 was used for the statistical analysis. Descriptive statistics and weighted mean were used. T-Test and One-way analysis of variance (ANOVA) were applied to determine differences in means among groups. Results Most of the participating nurses (55.7%) were male, while (44.3%) were female. The majority of nurses (84.4%) are under 40 years of age. The weighted mean scores in the pre-test ranged from 52.2 to 75.1% and the mean scores was (6.16 ± 1.97). After applying conventional BLS training, the weighted mean scores ranged from 85.6 to 97.3% and the mean scores was (9.19 ± 1.04). The study revealed that the nurses’ knowledge increased after applying simulation-based training program. The mean of knowledge scores was statistically significant between the pre and post-test on the basis of the current work hospital (P-value < 0.001). Conclusion This study affords significant evidence of the positive effects of the BLS training program in improving nurses’ knowledge; we recommend advanced BLS training for all healthcare providers, doctors, and nurses working in hospitals and healthcare centers. Nursing managers can implement systematic strategies to enhance nurses’ knowledge and practice in BLS to target low-scoring Governorates.